Electromyographic Patterns in Children presented as Floppy Baby: Experience in a Neurophysiology Laboratory of a Tertiary care hospital in Bangladesh - Debnath, Bithi; Hussain, Md Enayet; Saha, Narayan Chandra; Nayeem, Abu; Chowdhury, Rajib Nayan (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Electromyography (EMG) is an invaluable diagnostic tool to reach a diagnosis in patients with hypotonia. The objective of this study was to observe the EMG patterns in children presented as floppy baby. Methods: It was a cross-sectional study conducted in the neurophysiology department of the National Institute of Neurosciences and hospital over 4 years. Floppy children, aged 1 month to 5 years, referred to the laboratory for EMG were enrolled in the study. Hypotonia due to acute flaccid paralysis or children having drugs that could cause decreased muscle tone were excluded from the study. Thereafter, children were categorized into groups of central, peripheral, and uncategorized/mixed hypotonia. EMG was done in all patients and an electro-diagnostic impression was made. Results: Out of 72 patients, 54.17% were male and 45.83% were female. Their average age of performing EMG was 26.81±18.12 months. Clinically it was observed that central and peripheral hypotonia were present in 18.05% and 70.83% of cases respectively and in 11.11% of cases, hypotonia could not be differentiated. EMG revealed Spinal muscular atrophy (SMA) in 38.89% of cases, followed by myopathy (26.39%), peripheral neuropathy (9.72%), and neuromuscular disorder (2.78%). In 19.44% of cases, EMG findings remained normal. Conclusion: Hypotonia of peripheral origin was the most common EMG finding in floppy children. SMA is the commonest electro-diagnostic impression followed by myopathy. J Bangladesh Coll Phys Surg 2022; 40: 240-245